Design of a High Gain Yagi-Uda Antenna Array for VHF-Band Radar Applications - Al-Shammari, Basim K. J.; Hburi, Ismail Sh.; Naman, Hala A.; Alrikabi, Haider Th. Salim; Khazaal, Hasan F.; Neamha, Kdhim A.; Qasim, Ahmed J. (Engineering, Technology & Applied Science Research, 2024)
The radar of the Yagi-Uda antenna array offers useful traits for the detection of stealth targets. It employs the Very High Frequency (VHF) band, which has the advantage of counteracting stealth technology, as the shape of the target and the absorbing materials used for absorbing radar signals are less efficient against VHF. Moreover, the meter wavelength enables the radar to detect targets at distances exceeding those accessible to millimeter- and centimeter-wave radars. Nevertheless, the range of detection of this type of radar remains constrained and requires further development. The majority of current research is concentrated on the signal processing aspect, with less focus being placed on the antenna array. The antenna elements represent a crucial component of the radar station. This article presents a novel development of the traditional 16-element Yagi-Uda antenna array, which is commonly used in surveillance radar systems operating at a meter frequency band. The development is achieved through a modification of the previously mentioned antenna, which aims to increase the directivity of the antenna array, with a minimum cost and the same signal processing as the original antenna array platform. An additional two-row Yagi-Uda antenna array is proposed, comprising 14 elements in each row and an associated power unit. This modification is designed to enhance the pattern characteristics of the array. Simulation and measurement results for the pattern of the antenna indicate that the achieved gain for the proposed modification is more than 3 dB in compression compared to that of the traditional 16-element array.